Answer:
20
Step-by-step explanation:
Step-by-step explanation:
(-2xy^3)^3
(-2(4)(-1)^3)^3
(-2(4)(-1))^3
(8)^3
512
Step-by-step explanation:
Given
w(x) = - 3x - 4
Now
w(7) = - 3 * 7 - 4
= - 21 - 4
= - 25
Hope it will help :)❤
Average rate of change: r=[f(b)-f(a)]/(b-a)
r=-60→[f(b)-f(a)]/(b-a)=-60
b=5; f(b)=-213; a=1; f(a)=27
(-213-27)/(5-1)=(-240)/4=-60
Answer: The <span>two points in the table which create an interval with an average rate of change of -60 are:
x f(x)
1 27
5 -213</span>
That is called an equation